2006
DOI: 10.1111/j.1365-263x.2006.00715.x
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of fluid consumption in a sample of Saudi Arabian adolescents aged 12–13 years

Abstract: Both carbonated soft drink and fruit juice/drink accounted for the largest proportion of total fluid intake by the sampled Saudi adolescents to the detriment of nutritious milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 27 publications
(33 reference statements)
4
15
0
Order By: Relevance
“…Eleven of these studies only involved children (Sichert‐Hellert et al ., ; O'Connor et al ., ; Linardakis et al ., ; Barquera et al ., ; Coppinger et al ., ; Kyttälä et al ., ; Lasater et al ., ; Wiley, ; Fulgoni & Quann, ; Sichieri et al ., ; Van Lippevelde et al ., ), seven only involved adolescents (Du et al ., ; Bello & Al‐Hammad, ; Gómez‐Martínez et al ., ; Veitch et al ., ; Duffey et al ., ; Parker et al ., ; Ambrosini et al ., ), twenty‐one only involved adults (Henderson et al ., ; Elmadfa et al ., ; Hoare et al ., ; Garriguet, ; Max Rubner‐Institut, ; Kant et al ., ; De Francisco et al ., ; Dubuisson et al ., ; Brown et al ., ; Irish Universities Nutrition Alliance, ; Spanish Agency for Food Safety & Nutrition, ; Amcoff et al ., ; Armstrong et al ., ; Csémy et al ., ; Knudsen et al ., ; Ma et al ., ; Manz et al ., ; Drewnowski et al ., ; Gibson & Shirreffs, ; Malisova et al ., ; O'Connor et al ., ), twelve involved children and adolescents (Garriguet, ; Libuda et al ., ,b; Wang et al ., ; Lioret et al ., ; Clifton et al ., ; Hafekost et al ., ; Alexy et al ., ; Feferbaum et al ., ; O'Neil et al ., ; Grimes et al ., ; Powell & Nguyen, ), three involved adolescents and adults (De Vriese et al ., ; Barquera et al ., ; Paturi et al ., ), and eleven involved children, adolescents and adults (Turrini et al ., ; Storey et al ., ; Forshee et al ., ; Ribas‐Barba et al ., ; Lec...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven of these studies only involved children (Sichert‐Hellert et al ., ; O'Connor et al ., ; Linardakis et al ., ; Barquera et al ., ; Coppinger et al ., ; Kyttälä et al ., ; Lasater et al ., ; Wiley, ; Fulgoni & Quann, ; Sichieri et al ., ; Van Lippevelde et al ., ), seven only involved adolescents (Du et al ., ; Bello & Al‐Hammad, ; Gómez‐Martínez et al ., ; Veitch et al ., ; Duffey et al ., ; Parker et al ., ; Ambrosini et al ., ), twenty‐one only involved adults (Henderson et al ., ; Elmadfa et al ., ; Hoare et al ., ; Garriguet, ; Max Rubner‐Institut, ; Kant et al ., ; De Francisco et al ., ; Dubuisson et al ., ; Brown et al ., ; Irish Universities Nutrition Alliance, ; Spanish Agency for Food Safety & Nutrition, ; Amcoff et al ., ; Armstrong et al ., ; Csémy et al ., ; Knudsen et al ., ; Ma et al ., ; Manz et al ., ; Drewnowski et al ., ; Gibson & Shirreffs, ; Malisova et al ., ; O'Connor et al ., ), twelve involved children and adolescents (Garriguet, ; Libuda et al ., ,b; Wang et al ., ; Lioret et al ., ; Clifton et al ., ; Hafekost et al ., ; Alexy et al ., ; Feferbaum et al ., ; O'Neil et al ., ; Grimes et al ., ; Powell & Nguyen, ), three involved adolescents and adults (De Vriese et al ., ; Barquera et al ., ; Paturi et al ., ), and eleven involved children, adolescents and adults (Turrini et al ., ; Storey et al ., ; Forshee et al ., ; Ribas‐Barba et al ., ; Lec...…”
Section: Resultsmentioning
confidence: 99%
“…The highest consumption of regular fruit/soft drinks was observed among Australian (Clifton et al ., ; Hafekost et al ., ), Saudi Arabian (Bello & Al‐Hammad, ), American (Wang et al ., ), Dutch (Van Rossum et al ., ; Veitch et al ., ) and Brazilian (Feferbaum et al ., ) adolescents, and the lowest was observed among French (Bellisle et al ., ), Italian (Turrini et al ., ; Leclercq et al ., ) and Spanish (Gómez‐Martínez et al ., ) teenagers. The consumption of soft drinks increased over time among the British (Coppinger et al ., ; Ng et al ., ) and Americans (Forshee et al ., ; Storey et al ., ; Wang et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…Potential health problems associated with overconsumption of food rich in free sugar such as overweight, dental caries, and potential enamel erosion are well documented [20]. In Saudi Arabia, for example, carbonated beverages and canned fruit drinks represented 26% and 25% of daily fluid consumption by adolescents, respectively [21]. …”
Section: Methodsmentioning
confidence: 99%
“…5 A study done in Riyadh (capital of Saudi Arabia) reported that the intake of soft drinks and juices constituted 51% of total fluid intake among a sample of 12-13 year old adolescents. 6 Consumption of soft drinks and beverages lead to fall in salivary pH, decrease in salivary pH caused by a drink depends on its intrinsic pH value as well as the buffering capacity. 7 For enamel dissolution, a pH of 5.5 is usually regarded as 'critical pH' but loss of mineral may be initiated even at higher pHs.…”
Section: Introductionmentioning
confidence: 99%